Thermal Puffing Promoting the Synthesis of N-Doped Hierarchical Porous Carbon–CoO(x) Composites for Alkaline Water Reduction - Wei, Zhongzhe (ACS Omega, 2021)
[Image: see text] N-doped porous carbon-based catalysts hold great promise for hydrogen evolution reaction (HER) due to their plentiful cavity construction, high specific surface area, and flexible metal assemblies. Nevertheless, the cumbersome synthetic process and the use of highly corrosive chemicals greatly increase the production costs and pollutions. Herein, we report a facile and eco-friendly thermal puffing strategy, which imitates the popcorn forming process, for the fabrication of N-doped hierarchical porous carbon–CoO(x) catalysts. The results indicate that the well-developed porosity and high specific surface area (696 m(2) g(–1)) of CoO(x)–NC-1.0 are achieved during the thermal expansion. Impressively, the as-prepared CoO(x)–NC-1.0 with ultralow Co loading (0.67 wt %) presents admirable HER performance to drive 10 mA cm(–2) at an overpotential of 189 mV in the alkaline electrolyte. Especially, the activity of CoO(x)–NC-1.0 can be maintained for a continuous ∼70 h test. Such an excellent property of CoO(x)–NC not only derives from the hierarchical porous structure but is also due to the higher ratio of graphitic-N and pyridinic-N, which promotes the better electrical conductivity and formation of more active Co(0) for HER, respectively. Moreover, this strategy is applicable to the fabrication of other transition metal-based hierarchical porous composites, which opens new possibilities for exploring promising candidates to substituted commercial Pt/C.